PELAPORAN KINERJA INSTANSI PEMERINTAH DALAM PERSPEKTIF VALUE FOR MONEY - Sukma, Indra Puji; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to evaluate the presentation of government istitution performance accountability statement (LAKIP) and to measure the implementation of program and activity based on the Value for Money perspective. The research method has been done by using qualitative descriptive, this research applies secondary data and primary data. The data collection technique which has been applied in this research is interview and documentation. The result of the discussion and the analysis about the report of performance of government institution performance in Sukolilo district of Surabaya in 2016 shows that in realizing the performance accountability of the Sukolilo district of Surabaya has been generated by developedperformance assessment system by determining the economic performance to consider the budget (input) with budget realization. The effective performance when it is reviewed from the total output which has been generated to the input. The effective performance when it is reviewed from the output or outcome which has been succeeded in running the goals of the institution in achieving the expected program. Based on the performance measurement model which has been applied to measure the program implementation performance and activities which has been done by using economic, efficiency, and effectiveness can be used as standard of performance in the following periods. Even though, the performance statement of Sukolilo district of Surabaya has shown the achievement performance of economic, efficiency and effective in accordance with the expectation, nevertheless, the development of relevant performance statement modelby considering its relevancy to the goals of the program and the activities.Keywords: Accountability, Value for Money, Economic, Efficiency, Effectiveness.